The Role Of The Financial Information Service System (FISS) Financial Services Authority Inassessment Loans At Bank BJB KCP Surade - Malfinas, Ryan; Adji, Widwi Handari (Pascasarjana STIE Miftahul Huda, 2025)
This research focuses on efforts to mitigate credit risks and improve the quality of loan portfolios in areas with low levels of financial literacy. The method used is descriptive qualitative with data collection techniques through in-depth interviews, field observations, and documentation. The results of the study show that the use of the Financial Information Service System (FISS) helps in the process of verifying the character of prospective debtors, analyzing payment capacity, and assessing risks in credit historically. In addition, the system accelerates decision-making in granting credit and reduces the likelihood of Non-Performing Loans (NPLs). The problems are the lack of access to digital technology services, the weak public understanding of the history of credit emergence, and the increase in the capacity of officers are still quite serious obstacles. This research underlines FISS in certification as a banking information center that has an impact on credit assessment in a bank clearly and more effectively, and greatly contributes to banking risk control at the regional level.